Chemically strengthened glass and glass-ceramics and methods for producing the same
By adding specific crystals to the microcrystalline glass and optimizing the composition and heat treatment conditions, the problems of insufficient transparency and low productivity of the microcrystalline glass are solved, and the effect of strength and transparency is achieved, and the manufacturing temperature is reduced.
Patent Information
- Application Number
- CN202310397738.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-05-28
- Filing Date
- 2021-08-10
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2041-08-10
AI Technical Summary
The transparency of existing microcrystalline glasses is insufficient, and high temperature heat treatment leads to low productivity.
By adding Li3PO4 and Li4SiO4 crystals to the microcrystalline glass, the composition and heat treatment conditions of the glass are optimized, its transparency and chemical reinforcement characteristics are improved, and the manufacturing temperature is reduced.
Microcrystalline glass with excellent transparency and strength is achieved, with a large coefficient of thermal expansion and can be manufactured at lower temperatures, improving production efficiency.
Smart Images

Figure CN116444160B_ABST
Abstract
Description
[0001] This application is a divisional application of the Chinese patent application with application date of August 10, 2021 and application number 202180006588.X. Technical Field
[0002] The present invention relates to glass-ceramics and chemically strengthened glass and methods for producing the same. Background Art
[0003] Chemically strengthened glass is used as protective glass for portable terminals, etc. Chemically strengthened glass is glass in which a compressive stress layer is formed on the glass surface by, for example, contacting the glass with a molten salt containing alkali metal ions, thereby causing ion exchange between the alkali metal ions in the glass and the alkali metal ions in the molten salt.
[0004] Glass-ceramics is glass with crystals precipitated in it. Compared with amorphous glass without crystals, glass-ceramics is harder and less susceptible to damage. In addition, compared with amorphous glass, the so-called CT limit of chemically strengthened glass-ceramics is large, so it can have high strength while preventing breakage. However, compared with amorphous glass, the transparency of previous glass-ceramics is often insufficient.
[0005] For chemically strengthened glass, the greater the compressive stress formed on the surface, the higher the strength, but tensile stress (CT) is generated inside the chemically strengthened glass to offset the compressive stress formed. When CT is too large, the chemically strengthened glass will break violently when it breaks. The critical tensile stress value that can prevent violent breakage is called the CT limit.
[0006] Patent Document 1 describes an example in which glass-ceramics is chemically strengthened by subjecting it to an ion exchange treatment.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: International Publication No. 2019 / 022035 Summary of the invention
[0010] Problems to be solved by the invention
[0011] The glass-ceramics described in Patent Document 1 is excellent in transparency and chemical strengthening properties, but sometimes has insufficient transparency. In addition, since the heat treatment temperature required for melting and crystallization of glass raw materials is high, there are concerns about productivity.
[0012] The present invention provides amorphous glass with excellent transparency and strength and a large thermal expansion coefficient; microcrystalline glass with excellent transparency and chemical strengthening properties, a large thermal expansion coefficient and can be manufactured at a relatively low temperature; and chemically strengthened glass with excellent transparency and strength and a large thermal expansion coefficient.
[0013] Means used to solve problems
[0014] The present invention relates to a chemically strengthened glass, wherein the haze value of the chemically strengthened glass converted to a thickness of 0.7 mm is 0.5% or less, the surface compressive stress value of the chemically strengthened glass is 400 MPa or more, the compressive stress layer depth of the chemically strengthened glass is 70 μm or more, and the ST limit determined by the following test method is 18000 MPa·μm to 30000 MPa·μm, and the chemically strengthened glass contains Li 3 PO 4 Crystal and Li 4 SiO 4 At least one of the crystals or containing Li 3 PO 4 and Li 4 SiO 4 A solid solution crystal of either one or a glass-ceramic of a solid solution of both.
[0015] (Test method)
[0016] As the test glass plates, a plurality of test glass plates having different tensile stress integral values, i.e., ST values, were prepared by subjecting a 15 mm square, 0.7 mm thick, mirror-finished surface glass plate to chemical strengthening treatment under various conditions.
[0017] Using a Vickers testing machine, a diamond indenter with a tip angle of 90° was driven into the center of the test glass plate to break the glass plate, and the number of fragments was taken as the number of broken pieces. The test was started with a diamond indenter load of 1 kgf. If the glass plate did not break, the load was increased by 1 kgf at a time, and the test was repeated until the glass plate broke, and the number of fragments at the initial break was counted.
[0018] The number of broken pieces was plotted against the ST value of the test glass plate, and the ST value when the number of broken pieces reached 10 was read and used as the ST limit.
[0019] The present invention relates to a glass-ceramic, wherein the glass-ceramic is a glass containing Li 3 PO 4 Crystal and Li 4 SiO 4 At least one of the crystals or containing Li 3 PO 4and Li 4 SiO 4 A solid solution crystal of any one of the above or a microcrystalline glass of a solid solution of both of the above, wherein the haze value of the microcrystalline glass converted to a thickness of 0.7 mm is 0.5% or less, and the tensile stress integral value ST limit is 18000 MPa·μm or more.
[0020] The present invention relates to a glass-ceramic, wherein the glass-ceramic contains, in terms of mol % based on oxides:
[0021] 40%~70% SiO 2 ,
[0022] 10%~35%Li 2 O.
[0023] 1%~15%Al 2 O 3 ,
[0024] 0.5%~5%P 2 O 5 ,
[0025] 0.5%~5% ZrO 2 ,
[0026] 0~10% B 2 O 3 ,
[0027] 0~3% Na 2 O.
[0028] 0~1%K 2 O. and
[0029] 0~4% SnO 2 ,and
[0030] SiO 2 、Al 2 O 3 , P 2 O 5 and B 2 O 3 The total amount is 60% to 80%, and
[0031] Li 2 O、Na 2 O and K 2 The total amount of O relative to SiO 2 、Al 2 O 3 , P 2 O 5 and B 2 O 3The total amount ratio is 0.20~0.60, and Li 3 PO 4 or Li 4 SiO 4 as the main crystal.
[0032] The present invention relates to a method for producing glass-ceramics, wherein a heat treatment is performed to keep the glass at a temperature of 450° C. or higher and 800° C. or lower.
[0033] The glass contains, in mole % based on oxides:
[0034] 40%~70% SiO 2 ,
[0035] 10%~35%Li 2 O.
[0036] 1%~15%Al 2 O 3 ,
[0037] 0.5%~5%P 2 O 5 ,
[0038] 0.5%~5% ZrO 2 ,
[0039] 0~10% B 2 O 3 ,
[0040] 0~3% Na 2 O.
[0041] 0~1%K 2 O. and
[0042] 0~4% SnO 2 ,and
[0043] SiO 2 、Al 2 O 3 , P 2 O 5 and B 2 O 3 The total amount is 60% to 80%, and
[0044] Li 2 O、Na 2 O and K 2 The total amount of O relative to SiO 2 、Al 2 O 3 , P 2 O 5 and B2 O 3 The ratio of the total amount is 0.20~0.60.
[0045] In addition, the present invention provides a semiconductor support substrate, wherein the semiconductor support substrate comprises the above-mentioned amorphous glass, microcrystalline glass or chemically strengthened glass.
[0046] Effects of the Invention
[0047] The present invention can obtain an amorphous glass having excellent transparency and strength and a large thermal expansion coefficient. In addition, the present invention provides a microcrystalline glass having excellent transparency and chemical strengthening properties and a large thermal expansion coefficient. In addition, the present invention provides a chemically strengthened glass having excellent transparency and strength and a large thermal expansion coefficient. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 This is a diagram showing the results of X-ray diffraction of glass-ceramics.
[0049] Figure 2 This is a diagram showing the stress distribution of chemically strengthened glass.
[0050] Figure 3 This is a diagram showing a cross-sectional FE-SEM image of glass-ceramics. In the figure, white arrows indicate examples of precipitated crystals.
[0051] Figure 4 This is an explanatory diagram of a sample used for measuring the fracture toughness value K1c obtained by the DCDC method.
[0052] Figure 5 The stress enlargement coefficient K1 (unit: MPa·m 1 / 2 ) and the crack growth rate v (unit: m / s).
[0053] Figure 6 (A) and Figure 6 (B) represents a supporting glass according to one embodiment of the present invention bonded to a semiconductor substrate, Figure 6 (A) is a cross-sectional view before bonding. Figure 6 (B) is a cross-sectional view after bonding.
[0054] Figure 7 A cross-sectional view showing a multilayer substrate according to one embodiment of the present invention. DETAILED DESCRIPTION
[0055] In the present specification, unless otherwise specified, "to" indicating a numerical range is used to mean that the numerical values described before and after it are included as the lower limit and the upper limit.
[0056] In this specification, "amorphous glass" refers to glass in which no diffraction peak indicating crystals is observed by the powder X-ray diffraction method described later. "Microcrystalline glass" is glass in which crystals are precipitated by heating "amorphous glass", and it contains crystals. In this specification, "amorphous glass" and "microcrystalline glass" are sometimes collectively referred to as "glass". In addition, amorphous glass that becomes microcrystalline glass by heat treatment is sometimes referred to as "matrix glass of microcrystalline glass".
[0057] In this specification, for powder X-ray diffraction measurement, for example, CuKα rays are used to measure 2θ in the range of 10° to 80°, and when a diffraction peak appears, the precipitated crystal is identified by the Hanawalt method. In addition, the crystal identified by the peak group containing the peak with the highest integrated intensity in the crystal identified by the method is used as the main crystal. As a measuring device, for example, Smart Lab manufactured by Rigaku Corporation of Japan can be used.
[0058] Hereinafter, "chemically strengthened glass" refers to glass subjected to a chemical strengthening treatment, and "glass for chemical strengthening" refers to glass before subjected to a chemical strengthening treatment.
[0059] In this specification, unless otherwise specified, the glass composition is expressed in mol % based on oxides, and mol % is simply referred to as "%".
[0060] In the present specification, “substantially free of” means that the content is lower than the level of impurities contained in raw materials, etc., that is, it is not intentionally added. Specifically, for example, it is less than 0.1%.
[0061] In this specification, "stress distribution" refers to a distribution in which the compressive stress value is expressed with the depth from the glass surface as a variable. In the stress distribution, tensile stress is expressed as negative compressive stress.
[0062] The "compressive stress value (CS)" can be measured by thinning a cross section of the glass and analyzing the thinned sample using a birefringence imaging system. The birefringence imaging system birefringence stress gauge is a device that uses a polarized light microscope and a liquid crystal compensator to measure the magnitude of the delay caused by stress, such as the birefringence imaging system Abrio-IM manufactured by CRi.
[0063] In addition, sometimes scattered light photoelasticity can be used for measurement. In this method, light is incident from the surface of the glass and the polarized light of the scattered light is analyzed to measure CS. As a stress measuring instrument using scattered light photoelasticity, there is, for example, the scattered light photoelasticity stress meter SLP-2000 manufactured by Orihara Manufacturing Co., Ltd.
[0064] In this specification, the "compressive stress layer depth (DOL)" is the depth at which the compressive stress value is zero.0 , the compressive stress value at a depth of 50 μm is recorded as CS 50 In addition, “internal tensile stress (CT)” refers to the tensile stress value at a depth of 1 / 2 of the plate thickness t.
[0065] The "tensile stress integral value (ST value)" refers to the area integral of the tensile stress (negative compressive stress) relative to the depth of the sample from DOL to a depth of 1 / 2 of the plate thickness t. In chemically strengthened glass, when the ST value in the glass reaches a certain threshold or more, the number of fragments increases sharply when it breaks. This threshold is called the "ST limit."
[0066] In this specification, "ST limit" is measured by the following method.
[0067] (Method for determining ST limit)
[0068] As the test glass plates, a plurality of test glass plates having different ST values were prepared by subjecting a glass plate having a square size of 15 mm and a thickness of 0.7 mm and having a mirror-finished surface to chemical strengthening treatment under various conditions.
[0069] Using a Vickers testing machine, a diamond indenter with a tip angle of 90° was driven into the center of the test glass plate to break the glass plate, and the number of fragments was taken as the number of broken pieces. The test was started with a diamond indenter load of 1 kgf. If the glass plate did not break, the load was increased by 1 kgf at a time, and the test was repeated until the glass plate broke, and the number of fragments at the initial break was counted.
[0070] The number of broken pieces was plotted against the ST value of the test glass plate, and the ST value when the number of broken pieces reached 10 was read and used as the ST limit.
[0071] In this specification, "light transmittance" refers to the average transmittance of light with a wavelength of 380 nm to 780 nm. In addition, "haze value" is measured using a halogen lamp C light source in accordance with JIS K7136:2000.
[0072] In this specification, the "fracture toughness value Kc" is a value obtained by the IF method specified in JIS R1607:2015.
[0073] In this specification, the "fracture toughness value K1c" is measured by the DCDC method [reference: MYHe, MRTurner and A.G.Evans, Acta Metall. Mater. 43 (1995) 3453.]. Specifically, the fracture toughness value K1c is measured by the DCDC method [reference: MYHe, MRTurner and A.G.Evans, Acta Metall. Mater. 43 (1995) 3453.]. Figure 4 The sample of the shape shown and SHIMADZU Autograph AGS-X5KN were measured as Figure 5 The stress expansion coefficient K1 (unit: MPa·m 1 / 2 The K1-v curve of the relationship between the stress expansion rate v (unit: m / s) and the crack growth rate v (unit: m / s) is obtained. The data of region III are regressed and extrapolated using a first-order equation, and the stress expansion coefficient K1 of 0.1 m / s is taken as the fracture toughness value K1c.
[0074] In this specification, the term "semiconductor" may refer to not only a semiconductor wafer or semiconductor chip made of silicon or the like but also a composite body including a chip, a wiring layer, and a sealing resin.
[0075] In this specification, the crack initiation load (CIL) refers to the indentation load of the Vickers indenter at which the crack initiation rate is 50% when an indentation is made on a mirror-finished surface having a thickness of 0.7 mm or more using a Vickers indenter having a tip angle of 136°.
[0076] (CIL measurement method)
[0077] Prepare a plate of glass with a thickness of 0.7 mm and mirror-polished on both sides. Use a Vickers hardness tester to press the Vickers indenter for 15 seconds, then remove the Vickers indenter and observe how many cracks are generated from the corners of the indentation after 15 seconds. Measure the indentation load of the Vickers indenter at 10 gf, 25 gf, 50 gf, 100 gf, 200 gf, 300 gf, and 500 gf for 10 sheets of glass, and calculate the average number of cracks generated at each load. Use an S-type function to regress the relationship between load and number of cracks, and take the load with 2 cracks as CIL (gf). It should be noted that the atmospheric conditions for the measurement are an air temperature of 25°C and a dew point of -40°C.
[0078] <Chemically strengthened glass>
[0079] The chemically strengthened glass of the present invention (hereinafter, also referred to as the present strengthened glass) is typically a plate-shaped glass article, which may be a flat plate or a curved surface. In addition, it may have portions with different thicknesses. In addition, the chemically strengthened glass of the present invention is a glass article containing Li 3 PO 4 Crystal and Li 4 SiO 4 At least one of the crystals or containing Li 3 PO 4 and Li 4 SiO 4 A solid solution crystal of either or a solid solution glass of both. 3 PO 4 Crystal and Li 4 SiO4 At least one of the crystals or containing Li 3 PO 4 and Li 4 SiO 4 The solid solution crystal of either one or the microcrystalline glass of the solid solution of both will be described later.
[0080] When the chemically strengthened glass is in the form of a plate, the thickness (t) is preferably 3 mm or less, more preferably 2 mm or less, 1.6 mm or less, 1.1 mm or less, 0.9 mm or less, 0.8 mm or less, and 0.7 mm or less. In order to obtain sufficient strength by chemical strengthening treatment, the thickness (t) is preferably 0.3 mm or more, more preferably 0.4 mm or more, and further preferably 0.5 mm or more.
[0081] The haze value of the present tempered glass converted to a thickness of 0.7 mm is preferably 0.5% or less. The haze value and light transmittance of the present chemically tempered glass are substantially the same as those of the microcrystalline glass before chemical tempering, and therefore will be described in the section of the microcrystalline glass.
[0082] When the surface compressive stress value (CS 0 ) is 400 MPa or more, since it is not easy to break due to deformation such as warping, it is preferred. 0 It is more preferably 500 MPa or more, and even more preferably 600 MPa or more. 0 The larger the size, the higher the strength, but CS 0 If it is too large, it may break violently in the event of rupture, so CS 0 It is preferably 1200 MPa or less, and more preferably 1000 MPa or less.
[0083] When the DOL of the present strengthened glass is 70 μm or more, it is not easy to break even if damage occurs on the surface, so it is preferred. The DOL is more preferably 80 μm or more, further preferably 90 μm or more, and particularly preferably 100 μm or more. The larger the DOL, the less likely it is to break even if damage occurs, but in chemically strengthened glass, since tensile stress corresponding to the compressive stress formed near the surface is generated inside, it cannot be increased extremely. In the case of thickness t, the DOL is preferably less than t / 4, more preferably less than t / 5. In order to shorten the time required for chemical strengthening, the DOL is preferably less than 200 μm, more preferably less than 180 μm.
[0084] When the CT of the present tempered glass is 110 MPa or less, the scattering of fragments is suppressed when the chemically tempered glass breaks, so it is preferred. The CT is more preferably 100 MPa or less, and further preferably 90 MPa or less. On the other hand, when the CT is reduced, the surface compressive stress is reduced, and there is a tendency that it is difficult to obtain sufficient strength. Therefore, the CT is preferably 50 MPa or more, more preferably 55 MPa or more, and further preferably 60 MPa or more.
[0085] In order to improve the drop resistance, the ST value of the tempered glass is preferably 18000 MPa·μm or more, more preferably 20000 MPa·μm or more, further preferably 22000 MPa·μm or more, and most preferably 24000 MPa·μm or more. On the other hand, when the ST value is too large, glass pieces fly when broken, so it is preferably 30000 MPa·μm or less, more preferably 29000 MPa·μm or less, further preferably 28000 MPa·μm or less, and most preferably 27000 MPa·μm or less.
[0086] The basic composition of the tempered glass preferably contains, in terms of mol% based on oxides:
[0087] 40%~70% SiO 2 ,
[0088] 10%~35%Li 2 O. and
[0089] 1%~15%Al 2 O 3 .
[0090] Furthermore, the basic composition of the tempered glass more preferably contains, in terms of mol% based on oxides:
[0091] 40%~70% SiO 2 ,
[0092] 10%~35%Li 2 O.
[0093] 1%~15%Al 2 O 3 ,
[0094] 0.5%~5%P 2 O 5 ,
[0095] 0.5%~5% ZrO 2 ,
[0096] 0~10% B 2 O 3 ,
[0097] 0~3% Na 2 O.
[0098] 0~1%K 2 O. and
[0099] 0~4% SnO 2 ,and
[0100] SiO 2 、Al 2 O 3 , P 2 O 5 and B 2 O 3 The total amount is 60% to 80%.
[0101] Alternatively, the basic composition of the tempered glass more preferably contains, in terms of mol% based on oxides:
[0102] 50%~70% SiO 2 ,
[0103] 15%~30%Li 2 O.
[0104] 1%~10%Al 2 O 3 ,
[0105] 0.5%~5%P 2 O 5 ,
[0106] 0.5%~8% ZrO 2 ,
[0107] 0.1% to 10% MgO,
[0108] 0~5% Y 2 O 3 ,
[0109] 0~10% B 2 O 3 ,
[0110] 0~3% Na 2 O.
[0111] 0~1%K 2 O. and
[0112] 0~2% SnO 2 .
[0113] Here, "the basic composition of chemically strengthened glass" refers to the composition of the glass-ceramics before chemical strengthening. This composition will be described later. The composition of the present strengthened glass has a composition similar to that of the glass-ceramics before strengthening, except for the case where an extreme ion exchange treatment is performed. In particular, the composition of the deepest part from the glass surface is the same as the composition of the glass-ceramics before strengthening, except for the case where an extreme ion exchange treatment is performed.
[0114] In addition to the semiconductor support substrate described later, this tempered glass is also useful as the protective glass used in the electronic devices such as mobile devices such as mobile phones and smart phones. In addition, it is also useful for the protective glass of the electronic devices such as televisions, computers, touch panels, etc. that are not easy to carry for the purpose, the wall surface of the elevator wall, the wall surface of the building such as the house or the building (full screen display). In addition, it is also useful for the building materials such as window glass, the interior of the desktop, automobile or airplane, etc. or their protective glass and the housing with a curved surface shape. In addition, the glass-ceramics before strengthening and the amorphous glass before crystallization are also useful as semiconductor support substrate purposes.
[0115] The semiconductor support substrate refers to a substrate used in the field of semiconductor packaging. In the field of semiconductor packaging, in manufacturing, technologies such as wafer-level packaging (WLP) and panel-level packaging (PLP) have attracted attention (see Asahi Glass Research Report 67 (2017)). This technology is, for example, a technology that places a silicon chip on a glass substrate and seals it by molding with a sealing resin.
[0116] In this case, the supporting substrate is sometimes peeled off during the manufacturing process. As the supporting substrate, a glass substrate is widely used. Since the glass substrate is transparent, it can be peeled off by irradiating a laser beam. The glass substrate used as the supporting substrate is required to reduce warping by matching the thermal expansion of the semiconductor. In addition, it is also required to be difficult to break during the packaging process, and if it is broken, the fragments will not fly.
[0117] <Glass-ceramic>
[0118] The present glass-ceramics preferably contains Li 3 PO 4 Crystal and Li 4 SiO 4 By using these crystals as the main crystals, the light transmittance is improved and the haze is reduced.
[0119] The present glass-ceramics may contain Li 3 PO 4 Crystal and Li 4 SiO 4 Crystals of these two. Either one can be contained as the main crystal. Li 3 PO4 and Li 4 SiO 4 The solid solution crystal of Li 3 PO 4 and Li 4 SiO 4 A solid solution crystal of any one of the above is used as the main crystal.
[0120] It should be noted that Li 2 SiO 3 The crystal has poor chemical resistance, so it is preferred not to contain Li 2 SiO 3 Crystal.
[0121] Due to Li 3 PO 4 Crystal and Li 4 SiO 4 The crystal structures of the crystals are similar, so it is sometimes difficult to distinguish by powder X-ray diffraction measurement. That is, when measuring powder X-ray diffraction, diffraction peaks appear near 2θ=16.9°, 22.3°, 23.1°, and 33.9°. Since there are also cases where the amount of crystals is small and orientation occurs, it is sometimes impossible to confirm the peaks with low intensity and the peaks of specific crystal faces. In addition, in the case of two crystal solid solutions, 2θ sometimes shifts the peak position by about 1°.
[0122] When X-ray diffraction is measured within the range of 2θ=10° to 80°, the strongest diffraction peak of the present glass-ceramics preferably appears at 22.3°±0.2° or 23.1°±0.2°.
[0123] In order to improve mechanical strength, the crystallization rate of the present glass-ceramics is preferably 5% or more, more preferably 10% or more, further preferably 15% or more, and particularly preferably 20% or more. In order to improve transparency, the crystallization rate is preferably 70% or less, more preferably 60% or less, and further preferably 50% or less. From the perspective of easy heating and bending molding, a small crystallization rate is also excellent.
[0124] In order to improve the strength, the average particle size of the precipitated crystals of the present microcrystalline glass is preferably 5 nm or more, particularly preferably 10 nm or more. In order to improve the transparency, the average particle size is preferably 80 nm or less, more preferably 60 nm or less, further preferably 50 nm or less, particularly preferably 40 nm or less, and most preferably 30 nm or less. The average particle size of the precipitated crystals can be obtained from a transmission electron microscope (TEM) image or a FE-SEM image.
[0125] The thickness (t) of the present microcrystalline glass in the case of a plate is preferably 3 mm or less, and more preferably 2 mm or less, 1.6 mm or less, 1.1 mm or less, 0.9 mm or less, 0.8 mm or less, and 0.7 mm or less. In addition, in order to obtain sufficient strength brought about by chemical strengthening treatment, the thickness (t) is preferably 0.3 mm or more, more preferably 0.4 mm or more, and further preferably 0.5 mm or more.
[0126] In the case of a thickness of 0.7 mm, the light transmittance of the present microcrystalline glass is 85% or more, so when used as a protective glass for a portable display, it is easy to see the image on the display. The light transmittance is preferably 88% or more, and more preferably 90% or more. The higher the light transmittance, the more preferred, but it is usually 91% or less. In the case of a thickness of 0.7 mm, a light transmittance of 90% is equivalent to that of ordinary amorphous glass.
[0127] It should be noted that, when the actual thickness is not 0.7 mm, the light transmittance at 0.7 mm can be calculated based on the measured value according to the Lambert-Beer law. In addition, when the plate thickness t is greater than 0.7 mm, the plate thickness can be adjusted to 0.7 mm by grinding, etching, etc. and then measured.
[0128] In addition, when the thickness is 0.7 mm, the haze value is 0.5% or less, preferably 0.3% or less, more preferably 0.2% or less, further preferably 0.15% or less, particularly preferably 0.1% or less, most preferably 0.08% or less, and extremely preferably 0.05% or less. The smaller the haze value, the more preferred, but it is usually 0.01% or more. When the thickness is 0.7 mm, a haze value of 0.02% is equivalent to that of ordinary amorphous glass.
[0129] It should be noted that, when the total visible light transmittance of a glass-ceramic with a plate thickness of t [mm] is 100 × T [%] and the haze value is 100 × H [%], by citing the Lambert-Beer law and using the constant α, it can be expressed as T = (1-R) 2 ×exp(-αt). Using this constant α, dH / dt∝exp(-αt)×(1-H) is obtained.
[0130] That is, since it is considered that the haze value increases in proportion to the internal linear transmittance as the plate thickness increases, the haze value H in the case of 0.7 mm is 0.7 It can be calculated by the following formula.
[0131]
[0132] When the plate thickness t is larger than 0.7 mm, the plate thickness may be adjusted to 0.7 mm by grinding, etching, etc., and then measured.
[0133] The ST limit of the present glass-ceramics is preferably above 18000 MPa·μm. In order to improve the drop resistance by chemical strengthening, the ST limit is more preferably above 19000 MPa·μm, and further preferably above 20000 MPa·μm. Since the present glass-ceramics has a large ST limit, it becomes high-strength and not easily broken by chemical strengthening. The larger the ST limit, the more preferred, but it is usually below 30000 MPa·μm.
[0134] The present microcrystalline glass is obtained by crystallizing amorphous glass described later by heating it.
[0135] The present glass-ceramics preferably contains, in terms of mol % based on oxides:
[0136] 40%~70% SiO 2 ,
[0137] 10%~35%Li 2 O.
[0138] 1%~15%Al 2 O 3 ,
[0139] 0.5%~5%P 2 O 5 ,
[0140] 0.5%~5% ZrO 2 ,
[0141] 0~10% B 2 O 3 ,
[0142] 0~3% Na 2 O.
[0143] 0~1%K 2 O. and
[0144] 0~4% SnO 2 In this specification, the microcrystalline glass of the above composition is also referred to as "the present microcrystalline glass A".
[0145] Alternatively, the present glass-ceramics preferably contains, in terms of mol% based on oxides:
[0146] 50%~70% SiO 2 ,
[0147] 15%~30%Li 2 O.
[0148] 1%~10%Al 2 O 3 ,
[0149] 0.5%~5%P 2 O 5 ,
[0150] 0.5%~8% ZrO 2 ,
[0151] 0.1% to 10% MgO,
[0152] 0~5% Y 2 O 3 ,
[0153] 0~10% B 2 O 3 ,
[0154] 0~3% Na 2 O.
[0155] 0~1%K 2 O. and
[0156] 0~2% SnO 2 In this specification, the microcrystalline glass of the above composition is also referred to as "the present microcrystalline glass B".
[0157] In addition, the SiO content in the present glass-ceramics is preferably 2 、Al 2 O 3 , P 2 O 5 and B 2 O 3 The total amount of SiO is 60% to 80%. 2 、Al 2 O 3 , P 2 O 5 and B 2 O 3 It is a network-forming component of the glass (hereinafter, also referred to as NWF). Since the total amount of these NWFs is large, the strength of the glass is improved. This increases the fracture toughness value of the microcrystalline glass, so the total amount of NWF is preferably 60% or more, more preferably 63% or more, and particularly preferably 65% or more. However, glass with too much NWF becomes difficult to manufacture due to increased melting temperature, so it is preferably 80% or less, more preferably 75%, and more preferably 70% or less.
[0158] Li 2 O、Na 2 O and K 2The total amount of O is relative to NWF, i.e. SiO 2 、Al 2 O 3 , P 2 O 5 and B 2 O 3 The total amount ratio of Al is preferably 0.20 to 0.60. 2 O 3 Relative to Li 2 The content of O is higher than that of Al 2 O 3 / Li 2 When the ratio of O to the total amount of NWF is 0.0029 to 0.0075, the Young's modulus can be increased while maintaining the thermal expansion coefficient suitable for the supporting substrate of the semiconductor package with a large resin component, and the warping in the packaging process can be reduced. As a lower limit, it is preferably 0.0031 or more, and more preferably 0.0032 or more. As an upper limit, it is preferably 0.0064 or less, and more preferably 0.0051 or less. As a component for increasing the Young's modulus, Al 2 O 3 The most effective, but in addition, we can also list: MgO, ZrO 2 , Y 2 O 3 , Ga 2 O 3 , BeO, TiO 2 、 2 O 5 .
[0159] Li 2 O、Na 2 O and K 2 O is a network modifier, and reducing their ratio relative to NWF increases the gaps in the network, thereby improving impact resistance. 2 O、Na 2 O and K 2 The total amount of O is relative to NWF, i.e. SiO 2 、Al 2 O 3 , P 2 O 5 and B 2 O 3 The total amount ratio of Li is preferably 0.60 or less, more preferably 0.55 or less, and particularly preferably 0.50 or less. On the other hand, these components are essential components for chemical strengthening, so in order to improve the chemical strengthening characteristics, Li 2 O、Na 2 O and K 2The total amount of O is relative to NWF, i.e. SiO 2 、Al 2 O 3 , P 2 O 5 and B 2 O 3 The total amount ratio of is preferably 0.20 or more, more preferably 0.25 or more, particularly preferably 0.30 or more.
[0160] Hereinafter, the glass composition will be described.
[0161] In this amorphous glass, SiO 2 It is a component that forms the network structure of glass. 2 It is a component that improves chemical durability. SiO 2 The content of SiO is preferably 40% or more. 2 The content of SiO is more preferably 45% or more, further preferably 50% or more, particularly preferably 52% or more, and extremely preferably 54% or more. 2 The content of is preferably 70% or less, more preferably 68% or less, further preferably 66% or less, particularly preferably 64% or less.
[0162] Al 2 O 3 It is an essential component to increase the surface compressive stress generated by chemical strengthening. 2 O 3 The content of Al is preferably 1% or more, more preferably 2% or more, further preferably 3%, 5%, 5.5%, 6% or more, particularly preferably 6.5%, and most preferably 7% or more. On the other hand, in order to prevent the devitrification temperature of the glass from becoming too high, Al 2 O 3 The content of is preferably 15% or less, more preferably 12% or less, further preferably 10% or less, particularly preferably 9% or less, and most preferably 8% or less.
[0163] Li 2 O is a component that forms surface compressive stress through ion exchange and is an essential component of the main crystal. 2 The content of O is preferably 10% or more, more preferably 14% or more, more preferably 15% or more, further preferably 18% or more, particularly preferably 20% or more, and most preferably 22% or more. On the other hand, in order to stabilize the glass, Li 2 The content of O is preferably 35% or less, more preferably 32% or less, further preferably 30% or less, particularly preferably 28% or less, and most preferably 26% or less.
[0164] Na 2 O is a component that improves the solubility of glass. 2 O is not essential, but is 2 In the case of O 2 The content of O is preferably 0.5% or more, more preferably 1% or more, and particularly preferably 2% or more. 2 When there is too much O, crystals are not easily precipitated or the chemical strengthening properties are reduced. 2 The content of O is preferably 3% or less, more preferably 2.5% or less, further preferably 2% or less, and particularly preferably 1.5% or less.
[0165] K 2 O and Na 2 O is also a component that lowers the melting temperature of glass, and K 2 O. In the presence of K 2 In the case of O K 2 The content of O is preferably 0.5% or more, more preferably 0.8% or more, and further preferably 1% or more. 2 When O is too much, the chemical strengthening characteristics are reduced or the chemical durability is reduced, so K 2 The O content is preferably 1% or less, more preferably 0.8% or less, further preferably 0.6% or less, particularly preferably 0.5% or less, and most preferably 0.4% or less.
[0166] In order to improve the melting property of glass raw materials, Na 2 O and K 2 Total content of ONa 2 O+K 2 O is preferably 1% or more, more preferably 2% or more.
[0167] In addition, when K 2 O content relative to Li 2 O、Na 2 O and K 2 The total content of O (hereinafter referred to as R 2 O) ratio K 2 O / R 2 When O is 0.2 or less, the chemical strengthening characteristics can be improved and the chemical durability can be improved, which is preferable. 2 O / R 2 O is more preferably 0.15 or less, and further preferably 0.10 or less.
[0168] It should be noted that R 2 O is preferably 10% or more, more preferably 15% or more, and even more preferably 20% or more. 2O is preferably 29% or less, more preferably 26% or less.
[0169] P 2 O 5 For Li 3 PO 4 The constituent components of crystals are essential. In order to promote crystallization, P 2 O 5 The content of is preferably 0.5% or more, more preferably 1% or more, further preferably 1.5% or more, particularly preferably 2% or more, and extremely preferably 2.5% or more. 2 O 5 When the content is too high, phase separation is easy during melting, and the acid resistance is significantly reduced. 2 O 5 The content of is preferably 5% or less, more preferably 4.8% or less, further preferably 4.5% or less, particularly preferably 4.2% or less.
[0170] ZrO 2 It is a component that improves mechanical strength and chemical durability. In order to significantly increase CS, it is preferable to contain ZrO 2 .ZrO 2 The content of ZrO is preferably 0.5% or more, more preferably 1% or more, further preferably 1.5% or more, particularly preferably 2% or more, and most preferably 2.5% or more. 2 It is preferably 8% or less, more preferably 7.5% or less, further preferably 7% or less, and particularly preferably 6% or less. 2 When the content of ZrO is too high, the viscosity decreases due to the increase in devitrification temperature. In order to suppress the deterioration of moldability due to the decrease in viscosity, when the molding viscosity is low, ZrO 2 The content of is preferably 5% or less, more preferably 4.5% or less, and further preferably 3.5% or less.
[0171] In addition, in order to improve chemical durability, ZrO 2 / R 2 O is preferably 0.02 or more, more preferably 0.03 or more, further preferably 0.04 or more, particularly preferably 0.1 or more, and most preferably 0.15 or more. In order to improve the transparency after crystallization, ZrO 2 / R 2 O is preferably 0.6 or less, more preferably 0.5 or less, further preferably 0.4 or less, and particularly preferably 0.3 or less.
[0172] MgO is a component that stabilizes glass and improves mechanical strength and chemical resistance. 2 O3 In the case where the content is relatively small, it is preferred to contain MgO. The content of MgO is preferably 1% or more, more preferably 2% or more, further preferably 3% or more, and particularly preferably 4% or more. On the other hand, when MgO is added in an excessive amount, the viscosity of the glass decreases, and devitrification or phase separation is easily caused. Therefore, the content of MgO is preferably 10% or less, more preferably 9% or less, further preferably 8% or less, and particularly preferably 7% or less.
[0173] TiO 2 As a component that can promote crystallization, TiO 2 .TiO 2 Not essential, but useful in the presence of TiO 2 In the case of TiO 2 The content of TiO is preferably 0.2% or more, more preferably 0.5% or more. On the other hand, in order to suppress devitrification during melting, TiO 2 The content of is preferably 4% or less, more preferably 2% or less, and further preferably 1% or less.
[0174] SnO 2 It has the function of promoting the formation of crystal nuclei and can contain SnO 2 SnO 2 Not essential, but in the presence of SnO 2 In the case of SnO 2 The content of SnO is preferably 0.5% or more, more preferably 1% or more, further preferably 1.5% or more, and particularly preferably 2% or more. On the other hand, in order to suppress devitrification during melting, SnO 2 The content of is preferably 4% or less, more preferably 3.5% or less, further preferably 3% or less, and particularly preferably 2.5% or less.
[0175] Y 2 O 3 Y is a component that has the effect of preventing fragments from scattering when the chemically strengthened glass breaks. 2 O 3 .Y 2 O 3 The content of Y is preferably 1% or more, more preferably 1.5% or more, further preferably 2% or more, particularly preferably 2.5% or more, and extremely preferably 3% or more. On the other hand, in order to suppress devitrification during melting, 2 O 3 The content of is preferably 5% or less, more preferably 4% or less.
[0176] B 2 O 3 In order to improve the chipping resistance of the chemically strengthened glass or the chemically strengthened glass and to improve the melting property, B may be contained.2 O 3 In order to improve the solubility, 2 O 3 Case B 2 O 3 The content of B is preferably 0.5% or more, more preferably 1% or more, and further preferably 2% or more. 2 O 3 When the content of B is too high, ribs are generated during melting or phase separation is likely to occur, and the quality of the chemically strengthened glass is likely to decrease. 2 O 3 The content of B is preferably 10% or less. 2 O 3 The content of is more preferably 8% or less, further preferably 6% or less, and particularly preferably 4% or less.
[0177] BaO, SrO, MgO, CaO and ZnO are all components that improve the solubility of glass, and BaO, SrO, MgO, CaO and ZnO may be contained. When containing these components, the total content of BaO, SrO, MgO, CaO and ZnO (hereinafter referred to as BaO+SrO+MgO+CaO+ZnO) is preferably 0.5% or more, more preferably 1% or more, further preferably 1.5% or more, and particularly preferably 2% or more. On the other hand, in order to reduce the ion exchange rate, BaO+SrO+MgO+CaO+ZnO is preferably 8% or less, more preferably 6% or less, further preferably 5% or less, and particularly preferably 4% or less.
[0178] Among them, in order to increase the refractive index of the residual glass and approach the precipitated crystal phase to increase the light transmittance of the microcrystalline glass and reduce the haze value, BaO, SrO, and ZnO may be contained. In this case, the total content of BaO, SrO and ZnO (hereinafter referred to as BaO+SrO+ZnO) is preferably 0.3% or more, more preferably 0.5% or more, further preferably 0.7% or more, and particularly preferably 1% or more. On the other hand, these components sometimes reduce the ion exchange rate. In order to improve the chemical strengthening characteristics, BaO+SrO+ZnO is preferably 2.5% or less, more preferably 2% or less, further preferably 1.7% or less, and particularly preferably 1.5% or less.
[0179] La 2 O 3 , Nb 2 O 5 and Ta 2 O 5 Both are components that prevent fragments from scattering when chemically strengthened glass breaks. La can be contained to increase the refractive index. 2 O 3 , Nb2 O 5 and Ta 2 O 5 In the presence of these ingredients, La 2 O 3 , Nb 2 O 5 and Ta 2 O 5 The total content (hereinafter referred to as La 2 O 3 +Nb 2 O 5 +Ta 2 O 5 ) is preferably 0.5% or more, more preferably 1% or more, further preferably 1.5% or more, and particularly preferably 2% or more. In order to prevent the glass from losing clarity during melting, La 2 O 3 +Nb 2 O 5 +Ta 2 O 5 It is preferably 4% or less, more preferably 3% or less, further preferably 2% or less, and particularly preferably 1% or less.
[0180] In addition, CeO may be contained 2 . CeO 2 Sometimes the coloration is suppressed by oxidizing the glass. 2 In the case of CeO 2 The content of CeO is preferably 0.03% or more, more preferably 0.05% or more, and further preferably 0.07% or more. 2 The content of is preferably 1.5% or less, more preferably 1.0% or less.
[0181] When the tempered glass is colored for use, a coloring component may be added within a range that does not hinder the realization of the desired chemical strengthening properties. Examples of the coloring component include Co 3 O 4 、MnO 2 , Fe 2 O 3 、NiO、CuO、Cr 2 O 3 、V 2 O 5 、Bi 2 O 3 , SeO 2 , Er 2 O 3 、Nd 2 O 3 .
[0182] The content of the coloring components is preferably within a range of 1% or less in total. In order to further increase the visible light transmittance of the glass, it is preferred that these components are substantially not contained.
[0183] In order to improve the weather resistance against UV light, HfO can be added. 2 , Nb 2 O 5 、Ti 2 O 3 When HfO is added for the purpose of improving weather resistance to ultraviolet light, in order to suppress the influence on other properties, 2 , Nb 2 O 5 and Ti 2 O 3 The total content of is preferably 1% or less, more preferably 0.5% or less, and even more preferably 0.1% or less.
[0184] In addition, SO may be appropriately contained 3 , chlorides, fluorides as clarifiers during glass melting, etc. When the total content of the components that function as clarifiers is excessively added, it affects the strengthening characteristics and crystallization behavior. Therefore, it is preferably 2% or less, more preferably 1% or less, and further preferably 0.5% or less in terms of mass % based on oxides. There is no particular restriction on the lower limit, but typically, it is preferably 0.05% or more in total in terms of mass % based on oxides.
[0185] When using SO 3 SO as a clarifier 3 When the content of SO is too small, no effect can be observed, so SO is calculated as mass % based on oxide. 3 The content of SO is preferably 0.01% or more, more preferably 0.05% or more, and further preferably 0.1% or more. 3 SO as a clarifier 3 The content of is preferably 1% or less, more preferably 0.8% or less, and further preferably 0.6% or less.
[0186] When Cl is used as a clarifier, if the Cl content is excessively added, physical properties such as strengthening characteristics are affected, so the Cl content is preferably 1% or less, more preferably 0.8% or less, and further preferably 0.6% or less, in terms of mass % based on oxides. In addition, when Cl is used as a clarifier, if the Cl content is too low, no effect is observed, so the Cl content is preferably 0.05% or more, more preferably 0.1% or more, and further preferably 0.2% or more, in terms of mass % based on oxides.
[0187] When using SnO 2 SnO as a clarifier 2 When the content of SnO is excessively added, it affects the crystallization behavior. Therefore, based on the mass % of the oxide, SnO 2 The content of SnO is preferably 1% or less, more preferably 0.5% or less, and further preferably 0.3% or less. 2 SnO as a clarifier 2 When the content of SnO is too small, no effect can be observed. Therefore, based on the mass % of the oxide, SnO 2 The content of Mg is preferably 0.02% or more, more preferably 0.05% or more, and further preferably 0.1% or more.
[0188] Preferably does not contain As 2 O 3 In the presence of Sb 2 O 3 In the case of containing , it is preferably 0.3% or less, more preferably 0.1% or less, and most preferably not contained.
[0189] The fracture toughness value of the present glass-ceramics is high, and even if a large compressive stress is formed by chemical strengthening, it is not easy to cause severe fracture. When the fracture toughness value of the present glass-ceramics is preferably 0.81 MPa·m 1 / 2 More preferably, 0.83 MPa·m 1 / 2 More preferably, 0.85 MPa·m 1 / 2 When the fracture toughness value is above 1.5 MPa·m, the glass with high impact resistance can be obtained. The upper limit of the fracture toughness value of the present glass-ceramics is not particularly limited, but is typically 1.5 MPa·m 1 / 2 the following.
[0190] In order to suppress the warping during chemical strengthening treatment, the Young's modulus of the present glass-ceramics is preferably more than 80 GPa, more preferably more than 85 GPa, further preferably more than 90 GPa, and particularly preferably more than 95 GPa. The present glass-ceramics is sometimes used after grinding. In order to easily grind, the Young's modulus is preferably less than 130 GPa, more preferably less than 120 GPa, and more preferably less than 110 GPa.
[0191] In addition, if the Young's modulus of amorphous glass is more than 80GPa, warping can be suppressed even in the state of amorphous glass, so it is suitable for use as a semiconductor support substrate. Preferably more than 85GPa, more preferably more than 90GPa, more preferably more than 95GPa. In order to easily grind, the Young's modulus is preferably less than 130GPa, more preferably less than 120GPa, and more preferably less than 110GPa.
[0192] From the viewpoint of suppressing the generation of cracks when dropped, the indentation load value (CIL) at which the number of cracks of the present glass-ceramics is 2 is preferably 50 gf or more, more preferably 100 gf or more, further preferably 150 gf or more, and most preferably 200 gf or more.
[0193] <Amorphous glass>
[0194] The present glass-ceramics can be obtained by heat-treating the amorphous glass (the amorphous glass of the present invention) described below. The composition of the amorphous glass of the present invention is the same as the composition of the present glass-ceramics described above.
[0195] The amorphous glass of the present invention (hereinafter, also referred to as the present amorphous glass) preferably contains 40% to 70% of SiO in terms of mol% based on oxides. 2 10%~35%Li 2 O and 1% to 15% Al 2 O 3 .
[0196] As a preferred composition of the present amorphous glass, for example, the following composition can be cited: a composition containing 40% to 70% SiO in terms of mol% based on oxides. 2 10%~35%Li 2 O, 1% to 15% Al 2 O 3 , 0.5%~5%P 2 O 5 , 0.5% to 5% ZrO 2 , 0~10% B 2 O 3 ,0~3% Na 2 O, 0~1% K 2 O and 0-4% SnO 2 .
[0197] Alternatively, as a preferred composition of the present amorphous glass, for example, the following composition can be cited: a composition containing 50% to 70% of SiO in terms of mol% based on oxides. 2 15%~30%Li 2 O, 1% to 10% Al 2 O 3 , 0.5%~5%P 2 O 5 , 0.5% to 8% ZrO 2 , 0.1% to 10% MgO, 0 to 5% Y 2 O 3 , 0~10% B 2 O 3 ,0~3% Na 2O, 0~1% K 2 O and 0-2% SnO 2 .
[0198] The SiO 2 、Al 2 O 3 , P 2 O 5 and B 2 O 3 The total amount of Li is preferably 60% to 80%. 2 O、Na 2 O and K 2 The total amount of O relative to SiO 2 、Al 2 O 3 , P 2 O 5 and B 2 O 3 The total amount ratio of is preferably 0.20 to 0.60.
[0199] In order to prevent structural relaxation during chemical strengthening, the glass transition temperature Tg of the present amorphous glass is preferably 400° C. or higher, more preferably 450° C. or higher, and further preferably 500° C. or higher. In addition, the glass transition temperature Tg of the present amorphous glass is preferably 650° C. or lower, and more preferably 600° C. or lower.
[0200] The difference (Tx-Tg) between the glass transition temperature (Tg) obtained by crushing the amorphous glass and obtaining a DSC curve using a differential scanning calorimeter and the crystallization start temperature (Tx) appearing in the lowest temperature region in the DSC curve is preferably 50° C. or more, more preferably 60° C. or more, further preferably 70° C. or more, and particularly preferably 80° C. or more. When (Tx-Tg) is large, it is easy to reheat the microcrystalline glass and perform bending processing, etc.
[0201] The average thermal expansion coefficient of the amorphous glass at 50°C to 350°C is preferably 70×10 -7 / °C or more, more preferably 75×10 -7 / ℃ or above, most preferably 80×10 -7 / ℃ or above.
[0202] When the thermal expansion coefficient is too large, cracks may occur during the chemical strengthening process due to the thermal expansion difference. Therefore, it is preferably 120×10 -7 / °C or less, more preferably 110×10 -7 / °C or less, more preferably 100×10 -7 / ℃ below.
[0203] In addition, when the thermal expansion coefficient is such, it is suitable as a supporting substrate for a semiconductor package having a large resin component.
[0204] <Method for producing chemically strengthened glass>
[0205] The chemically strengthened glass of the present invention is produced by subjecting glass-ceramics to a chemical strengthening treatment. The glass-ceramics is produced by subjecting the aforementioned amorphous glass to a heat treatment to crystallize the amorphous glass.
[0206] (Manufacture of amorphous glass)
[0207] Amorphous glass can be produced, for example, by the following method. It should be noted that the production method described below is an example of producing a plate-shaped chemically strengthened glass.
[0208] Glass raw materials are mixed to obtain glass of preferred composition, and heated and melted in a glass melting furnace. Then, the molten glass is homogenized by bubbling, stirring, adding a clarifier, etc., and formed into a glass plate of a specified thickness by a known forming method, and then slowly cooled. Alternatively, the molten glass can be formed into a plate by the following method: forming the molten glass into a block, slowly cooling it, and then cutting it.
[0209] (Crystallization treatment)
[0210] The amorphous glass obtained through the above-mentioned operation steps is subjected to a heat treatment (for example, preferably at 450° C. or higher and 800° C. or lower) to obtain microcrystalline glass.
[0211] The heat treatment may be performed by a two-step heat treatment, wherein the temperature is raised from room temperature to a first treatment temperature and maintained for a certain period of time, and then maintained for a certain period of time at a second treatment temperature higher than the first treatment temperature. Alternatively, the heat treatment may be performed by a one-step heat treatment, wherein the temperature is maintained at a specific treatment temperature and then cooled to room temperature.
[0212] In the case of a two-step heating treatment, the first treatment temperature is preferably a temperature region where the crystal nucleation rate increases for the glass composition, and the second treatment temperature is preferably a temperature region where the crystal growth rate increases for the glass composition. In addition, for the holding time at the first treatment temperature, it is preferably held for a long time so that a sufficient number of crystal nuclei are generated. By generating a large number of crystal nuclei, the size of each crystal is reduced, thereby obtaining a microcrystalline glass with high transparency.
[0213] In the case of a two-step treatment, for example, the first treatment temperature is 450°C to 700°C for 1 to 6 hours, and then the second treatment temperature is 600°C to 800°C for 1 to 6 hours. In the case of a one-step treatment, for example, the temperature is 500°C to 800°C for 1 to 6 hours.
[0214] The molten glass may be homogenized and formed into a glass plate of a predetermined thickness, or the molten glass may be formed into a block and then continuously crystallized.
[0215] When a plate-shaped glass is subjected to heat treatment, examples of the support plate include silicon carbide plates, silicon nitride plates, SiN plates, alumina plates, mullite cordierite plates, mullite plates, and microcrystalline glass plates. In addition, in order to reduce temperature unevenness during heat treatment, a material with high thermal conductivity is preferred. The thermal conductivity of the support plate is preferably 2 W / (m·K) or more, more preferably 20 W / (m·K) or more, and further preferably 40 W / (m·K) or more.
[0216] In order to prevent the glass from adhering to the support plate, a release agent may be used. Examples of the release agent include alumina cloth and glass cloth. In addition, examples include powdered boron nitride, alumina, minerals, etc. The powdered release agent may be mixed with a solvent and applied by spraying or the like. When a granular release agent is used, the average particle size is preferably 80 μm or less, more preferably 50 μm or less, and further preferably 30 μm or less.
[0217] When heat treating the glass, the glass may be laminated to improve the operation efficiency. When laminating, a release agent is preferably used between the glass and the glass. In addition, a support plate may be placed between the glass and the glass.
[0218] The microcrystalline glass obtained by the above operation steps is ground and polished as needed to form a microcrystalline glass plate. When the microcrystalline glass plate is cut into a specified shape and size or chamfered, if the cutting and chamfering are performed before the chemical strengthening treatment, a compressive stress layer is also formed on the end face by the subsequent chemical strengthening treatment, which is preferred.
[0219] (Chemical strengthening treatment)
[0220] The chemical strengthening treatment is a treatment in which the glass is brought into contact with the metal salt by immersing the glass in a molten solution of a metal salt (e.g., potassium nitrate) containing metal ions with a large ionic radius (typically Na ions or K ions), thereby replacing the metal ions with a small ionic radius (typically Na ions or Li ions) in the glass with metal ions with a large ionic radius (typically Na ions or K ions for Li ions, and K ions for Na ions).
[0221] In order to speed up the chemical strengthening treatment, it is preferred to use "Li-Na exchange" in which Li ions in the glass are exchanged with Na ions. In addition, in order to form a large compressive stress by ion exchange, it is preferred to use "Na-K exchange" in which Na ions in the glass are exchanged with K ions.
[0222] As molten salts for chemical strengthening treatment, for example, nitrates, sulfates, carbonates, chlorides, etc. can be cited. Among them, as nitrates, for example, lithium nitrate, sodium nitrate, potassium nitrate, cesium nitrate, silver nitrate, etc. can be cited. As sulfates, for example, lithium sulfate, sodium sulfate, potassium sulfate, cesium sulfate, silver sulfate, etc. can be cited. As carbonates, for example, lithium carbonate, sodium carbonate, potassium carbonate, etc. can be cited. As chlorides, for example, lithium chloride, sodium chloride, potassium chloride, cesium chloride, silver chloride, etc. can be cited. These molten salts can be used alone or in combination.
[0223] Regarding the treatment conditions of the chemical strengthening treatment, the time and temperature can be selected in consideration of the glass composition, the type of molten salt, etc. For example, it can be listed as follows: the present microcrystalline glass is preferably subjected to a chemical strengthening treatment for preferably less than 1 hour at a temperature below 450°C. Specifically, for example, it can be listed as follows: preferably, the treatment is preferably immersed in a molten salt containing 0.3% by mass of Li and 99.7% by mass of Na (for example, a mixed salt of lithium nitrate and sodium nitrate) at 450°C for about 0.5 hours.
[0224] The chemical strengthening treatment can utilize two-step ion exchange, for example, in the following manner. First, the present microcrystalline glass is preferably immersed in a metal salt containing Na ions (e.g., sodium nitrate) at about 350°C to about 500°C for about 0.1 hour to about 10 hours. As a result, ion exchange between the Li ions in the microcrystalline glass and the Na ions in the metal salt occurs, and a relatively deep compressive stress layer can be formed.
[0225] Next, it is preferably immersed in a metal salt containing K ions (e.g., potassium nitrate) at about 350°C to about 500°C for about 0.1 hour to about 10 hours. As a result, a large compressive stress is generated in a portion within a depth of about 10 μm, for example, of the compressive stress layer formed by the previous treatment. According to such a two-step treatment, a stress distribution with a large surface compressive stress value is easily obtained.
[0226] <Semiconductor support substrate>
[0227] The semiconductor support substrate of the present invention (hereinafter sometimes referred to as support glass) is described. The semiconductor support substrate of the present invention includes the amorphous glass or microcrystalline glass of the present invention. In order to improve the strength, it is more preferable to include the tempered glass of the present invention.
[0228] The amorphous glass, microcrystalline glass or tempered glass has a large coefficient of thermal expansion and is therefore suitable for use as a support substrate for fan-out packages. In fan-out packages, packages with various average thermal expansion coefficients are formed according to the ratio of semiconductor chips to resin components. However, in recent years, there is sometimes a demand to improve the fluidity of the molding resin and reduce filling defects, so packages with a large resin component and a high average thermal expansion coefficient are mostly used.
[0229] Figure 6 (A) and Figure 6 (B) is an example of a cross-sectional view of a support glass bonded to a semiconductor substrate. Figure 6 The supporting glass G1 shown in (A) is bonded to the conductive substrate 10 at a temperature of 200° C. to 400° C. via a peeling layer 20 (which may also function as a bonding layer), thereby obtaining Figure 6 (B) shows a laminated substrate 30. As the semiconductor substrate 10, for example, a full-size semiconductor wafer, a semiconductor chip, a substrate obtained by molding a semiconductor chip with resin, a wafer with elements formed thereon, etc. can be used. The peeling layer 20 is, for example, a resin that can withstand a temperature of 200°C to 400°C.
[0230] This support substrate is used by bonding with a semiconductor substrate. For example, it can be used for support glass for fan-out wafer-level packaging, support glass for image sensors such as MEMS, CMOS, and CIS that effectively miniaturize components by wafer-level packaging, support glass with through holes (glass interposer; GIP), and support glass for semiconductor back grinding. This support glass is particularly suitable as support glass for fan-out wafer-level and panel-level packaging.
[0231] Figure 7 This is an example of a cross-sectional view of a laminated substrate in which the present supporting glass is used as a supporting substrate for a fan-out wafer-level package.
[0232] In a fan-out chip-level package, for example, at a temperature of 200°C to 400°C, the support glass G2 and the semiconductor substrate 40 are stacked via a peeling layer 50 such as a resin (which can also serve as a bonding layer). In addition, a stacked substrate 70 is obtained by embedding the semiconductor substrate 40 with a resin 60. Then, for example, ultraviolet rays are laser-irradiated to the peeling layer 50 through the support glass G2, thereby peeling the support glass G2 from the semiconductor substrate 40 embedded with the resin 60. The support glass G2 can be reused. The semiconductor substrate 40 embedded with the resin 60 is wired by copper wires or the like. In addition, copper wires or the like can also be wired in advance on the peeling layer. It should be noted that a substrate obtained by embedding a semiconductor chip with a resin 60 can also be used as a semiconductor substrate.
[0233] Since the present supporting substrate has high light transmittance, it is possible to effectively utilize visible light laser or ultraviolet laser having high energy as the laser used for the lift-off.
[0234] [Example]
[0235] Hereinafter, the present invention will be described by way of examples, but the present invention is not limited thereto.
[0236] [Experimental Example 1]
[0237] <Production and evaluation of amorphous glass>
[0238] Glass raw materials were prepared to obtain the glass compositions in terms of mol% based on oxides in Tables 1 to 2, and weighed to obtain 800 g of glass. The mixed glass raw materials were then placed in a platinum crucible, put into an electric furnace at 1600° C., melted for about 5 hours, degassed, and homogenized.
[0239] The obtained molten glass was poured into a mold, kept at a temperature of the glass transition temperature for 1 hour, and then cooled to room temperature at a rate of 0.5°C / min to obtain a glass block. The glass transition temperature, specific gravity, Young's modulus, fracture toughness value, and thermal expansion coefficient of the amorphous glass were evaluated using a portion of the obtained block, and the obtained results are shown in Tables 1 and 2.
[0240] Blank columns in the table indicate no evaluation. 2 O represents Li 2 O、Na 2 O and K 2 Total content of O, NWF represents SiO 2 、Al 2 O 3 , P 2 O 5 and B 2 O 3 The total content of .
[0241] G3 to G8, G11, G13, and G14 are examples of the amorphous glass of the present invention, and G1, G2, G9, G10, G12, G15, and G16 are comparative examples.
[0242] (Specific gravity ρ)
[0243] The measurement was performed using the Archimedean method.
[0244] (Glass transition temperature Tg)
[0245] The glass was crushed using an agate mortar, and about 80 mg of the powder was placed in a platinum pool. The temperature was raised from room temperature to 1100°C at a heating rate of 10 / min. A differential scanning calorimeter (manufactured by Bruker; DSC3300SA) was used to measure the DSC curve and the glass transition temperature Tg was determined.
[0246] Alternatively, based on JIS R1618:2002, a thermal expansion curve was obtained using a thermal dilatometer (manufactured by Bruker AXS; TD5000SA) at a heating rate of 10°C / min, and the glass transition temperature Tg [unit: °C] and the thermal expansion coefficient [unit: 1 / K] were determined from the obtained thermal expansion curve.
[0247] (Haze value)
[0248] The haze value [unit: %] under a halogen lamp C light source was measured using a haze meter (manufactured by Suga Test Instruments; HZ-V3).
[0249] (Young's modulus E)
[0250] The measurement was carried out by an ultrasonic pulse method (JIS R1602).
[0251] (Fracture toughness value Kc)
[0252] The measurement was performed by the IF method in accordance with JIS R1607:2015.
[0253]
[0254]
[0255] <Crystallization treatment and evaluation of glass-ceramics>
[0256] The obtained glass block was processed into 50 mm×50 mm×1.5 mm, and then heat treated under the conditions described in Tables 3 and 4 to obtain microcrystalline glass. In the crystallization conditions column in the table, the upper row is the nucleation treatment conditions, and the lower row is the crystal growth treatment conditions. For example, when the upper row is recorded as 550°C for 2 hours and the lower row is recorded as 730°C for 2 hours, it means that it is kept at 550°C for 2 hours and then kept at 730°C for 2 hours.
[0257] The effect of the release agent was confirmed in the crystallization process. When the glass of G13 was heat-treated on the support plate of the alumina plate without using a release agent, the glass adhered to the support plate. When boron nitride was used as a release agent, the glass did not adhere to the support plate, and microcrystalline glass was obtained. When alumina cloth, alumina sheets, alumina particles, glass cloth, and talc were used as release agents, no adhesion between the glass and the support plate occurred, and microcrystalline glass was obtained.
[0258] Alumina sheets were used as release agents, and SiC plates, alumina plates, mullite-cordierite plates, and mullite plates were used as support plates to heat treat the G13 glass, and as a result, microcrystalline glass was obtained.
[0259] Examples 4, 5, 7, 9, 12 to 14 are embodiments, and Examples 1 to 3, 6, 8, 10, and 11 are comparative examples.
[0260] The obtained microcrystalline glass was processed and mirror-polished to obtain a microcrystalline glass plate with a thickness t of 0.7 mm. In addition, a rod-shaped sample was prepared for measuring the thermal expansion coefficient. A portion of the remaining microcrystalline glass was crushed for analysis of precipitated crystals. The evaluation results of the microcrystalline glass are shown in Tables 3 to 4. Blank columns indicate no evaluation.
[0261] (X-ray diffraction: precipitated crystals)
[0262] Powder X-ray diffraction was measured under the following conditions to identify the precipitated crystals.
[0263] Measuring device: Made by Rigaku Corporation, Smart Lab
[0264] X-rays used: CuKα rays
[0265] Measuring range: 2θ = 10° to 80°
[0266] Speed: 1° / min
[0267] Step distance: 0.01°
[0268] The detected main crystals are shown in the crystal column of Tables 3 to 4. 3 PO 4 and Li 4 SiO 4 Since it is difficult to distinguish by powder X-ray diffraction, both are recorded at the same time. Figure 1 2 shows the results of measuring the microcrystalline glass of Example 4 by X-ray diffraction.
[0269] (Haze value)
[0270] The haze value [unit: %] under a halogen lamp C light source was measured using a haze meter (manufactured by Suga Test Instruments; HZ-V3).
[0271] (CIL)
[0272] Prepare a plate-shaped glass with a thickness of 0.7 mm and mirror-polished on both sides. Use a Vickers hardness tester to press the Vickers indenter (the angle of the front end is 136°) for 15 seconds, then remove the Vickers indenter and observe the vicinity of the indentation after 15 seconds. During the observation, it was studied how many cracks were generated from the corners of the indentation. The indentation loads of the Vickers indenter of 10gf, 25gf, 50gf, 100gf, 200gf, 300gf, and 500gf were measured on 10 sheets of glass respectively. According to each load, the average number of cracks generated was calculated. The relationship between the load and the number of cracks was regressed using an S-type function. According to the regression calculation results, the load with 2 cracks was taken as the above-mentioned indentation load value (gf). It should be noted that the atmospheric conditions for the measurement were an air temperature of 25°C and a dew point of -40°C.
[0273] (ST Limit)
[0274] As the test glass plates, a plurality of test glass plates having different ST values were prepared by subjecting a glass plate having a square size of 15 mm and a thickness of 0.7 mm and a mirror-finished surface to chemical strengthening treatment under various conditions.
[0275] Using a Vickers testing machine, a diamond indenter with a tip angle of 90° was driven into the center of the test glass plate to break the glass plate, and the number of fragments was taken as the number of broken pieces. The test was started with a diamond indenter load of 1 kgf, and if the glass plate did not break, the load was increased by 1 kgf each time, and the test was repeated until the glass plate broke, and the number of broken pieces at the initial break was counted.
[0276] The number of broken pieces was plotted against the ST value of the test glass plate, and the ST value when the number of broken pieces reached 10 was read and used as the ST limit.
[0277]
[0278] Table 4
[0279]
[0280] The heat treatment conditions of G5 in Examples 5 and 6 shown in Tables 3 and 4 are different, and the heat treatment conditions of G6 in Examples 7 and 8 are different. From the comparison between Examples 5 and 6 and between Examples 7 and 8, it can be seen that for the microcrystalline glass of the present invention, even if the composition is the same, the precipitated crystals change by changing the heat treatment temperature and show different haze. The microcrystalline glass of the present invention precipitates Li 3 PO 4 or Li 4 SiO 4 , the haze is reduced, showing excellent transparency.
[0281] <Evaluation of chemical strengthening treatment and strengthened glass>
[0282] The glass-ceramics of Examples 4 and 14 were chemically strengthened by the following method and designated as Examples 15 and 16, respectively. Examples 15 and 16 are embodiments. A molten salt containing 0.3 mass % of lithium nitrate and 99.7 mass % of sodium nitrate was used as a strengthening salt, and an ion exchange treatment was performed at 450°C for 30 minutes to obtain a chemically strengthened glass. The stress distribution of the obtained chemically strengthened glass was measured using a scattered light photoelastic stress meter SLP-2000 manufactured by Orihara Manufacturing Co., Ltd. The results are shown in Table 5. In Table 5, the glass-ceramics of glass G4 is indicated as GC4, and the glass-ceramics of glass G14 is indicated as GC14. In addition, in Figure 2 Graph 2 shows the stress distribution of chemically strengthened glass S1 obtained by chemically strengthening the glass-ceramics of Example 4. FIG.
[0283] Table 5
[0284]
[0285] As shown in Table 5, the chemically strengthened glass of the present invention is excellent in transparency and strength.
[0286] [Experimental Example 2]
[0287] <Production and evaluation of amorphous glass>
[0288] Amorphous glass having the glass composition shown in Table 6 in terms of mol % based on oxides was prepared in the same manner as in Experimental Example 1, and its properties were evaluated. The fracture toughness value K1c was evaluated by the following method. The results are shown in Table 6.
[0289] (Fracture toughness value K1c)
[0290] The fracture toughness value K1c (unit: MPa·m 1 / 2 ). Referring to the method described in MYHe, MRTurner and AGEvans, Acta Metall. Mater. 43 (1995) 3453., the DCDC method was used. Figure 4 The sample with the shape shown and SHIMADZU Autograph AGS-X5KN were measured as follows Figure 5 The stress expansion coefficient K1 (unit: MPa·m 1 / 2 The K1-v curve of the relationship between the stress expansion rate v (unit: m / s) and the crack growth rate v (unit: m / s) is obtained. The data of region III are regressed and extrapolated using a first-order equation, and the stress expansion coefficient K1 of 0.1 m / s is taken as the fracture toughness value K1c.
[0291]
[0292] <Crystallization treatment and evaluation of glass-ceramics>
[0293] Glass-ceramics were obtained in the same manner as in Experimental Example 1, and the properties thereof were evaluated. However, X-ray diffraction was evaluated under the following conditions.
[0294] (X-ray diffraction: precipitated crystals)
[0295] Powder X-ray diffraction was measured under the following conditions to identify the precipitated crystals.
[0296] Measuring device: Made by Rigaku Corporation, Smart Lab
[0297] X-rays used: CuKα rays
[0298] Measuring range: 2θ = 10° to 80°
[0299] Speed: 10° / min
[0300] Step distance: 0.02°
[0301] The results are shown in Table 7. In Table 7, Examples 18 to 27 are Examples, and Example 17 is a Comparative Example.
[0302]
[0303] As shown in Table 7, the glass of the present invention has a small haze value and excellent transparency.
[0304] The chemical resistance of Example 2 in Table 3 and Example 21 in Table 7 was evaluated. The samples were immersed in HCl at pH 1 for 1 minute at room temperature, and then immersed in NaOH at pH 12.5 at 65°C for 6 minutes. The haze and transmittance were then measured. The haze of Example 2 increased to 0.73%, and the transmittance at 550 nm decreased by 4.8%. On the other hand, in Example 21, the haze was 0.03%, which was almost unchanged, and the transmittance at 550 nm decreased by only 0.7%. It can be seen that with the precipitation of Li 2 SiO 3 Compared with the crystal of Example 2, Li 3 PO 4 Crystal Example 21 was excellent in chemical resistance.
[0305] [Experimental Example 3]
[0306] <Production and evaluation of amorphous glass>
[0307] In the same manner as in Example 1, amorphous glass having the glass composition shown in Table 8 in terms of mol% based on oxides was prepared, and its properties were evaluated. However, SO added as a clarifier 3 、Cl、SnO 2 The results are shown in Table 8.
[0308] Table 8
[0309] Mole % G29 G30 G31 G32 G33 G34 <![CDATA[SiO 2 ]]> 61 61 61 61 61 61 <![CDATA[Al 2 THE 3 ]]> 5 5 5 5 5 5 <![CDATA[Li 2 The]]> 21 21 21 21 21 21 <![CDATA[Na 2 The]]> 2 2 2 2 2 2 <![CDATA[K 2 The]]> 0 0 0 0 0 0 CaO 0 0 0 0 0 0 <![CDATA[P 2 THE 5 ]]> 2 2 2 2 2 2 <![CDATA[B 2 THE 3 ]]> 0 0 0 0 0 0 MgO 5 5 5 5 5 5 <![CDATA[ZrO 2 ]]> 3 3 3 3 3 3 <![CDATA[Y 2 THE 3 ]]> 1 1 1 1 1 1 <![CDATA[SO 3 (Weight %)]]> 0.3 0.3 0 0 0 0 Cl (wt%) 0 0 1 1 0.5 1 <![CDATA[SnO 2 (Weight %)]]> 0.05 0.1 0.05 0.1 0 0 <![CDATA[ρ(g / cm 3 )]]> 2.56 2.56 2.56 2.56 2.56 2.56 Tg(℃) 513 Haze(%) 0.02 0.02 0.02 0.02 0.02 0.02 E(GPa) 90 90 90 90 90 90 <![CDATA[Kc(MPa·m 1 / 2 )]]> 0.95 0.95 0.95 0.95 0.95 0.95 <![CDATA[K1c(MPa·m 1 / 2 )]]> 0.85 0.85 0.85 0.85 0.85 0.85
[0310] <Crystallization treatment and evaluation of glass-ceramics>
[0311] Glass-ceramics were obtained in the same manner as in Example 1, and the properties thereof were evaluated. The results are shown in Table 9. In Table 9, Examples 28 to 33 are all Examples.
[0312] Table 9
[0313]
[0314] As shown in Table 9, it can be seen that for the glass of the present invention, even if the clarifier SO is added alone or in combination, 3 、Cl、SnO 2 It will not affect the optical and mechanical properties.
[0315] The polishing rates of the amorphous glass and the glass of the present invention are shown in Table 10. Example 34 is a comparative example, and Examples 4 and 21 are examples.
[0316] Table 10
[0317]
[0318] As shown in Table 10, it can be seen that the glass of the present invention has a higher polishing rate after crystallization than ordinary amorphous glass and is excellent in processability.
[0319] Figure 3 The cross-sectional FE-SEM image of Example 21 is shown in Figure 21. Figure 3 In the figure, the white arrows indicate the example of precipitated crystals. It can be seen that the size of the precipitated crystals measured under the following conditions is 20nm to 50nm. Since the crystal size is small, it is not easily affected by scattering and has excellent optical properties.
[0320] Apparatus: The measurement was performed using JSM-7800F Prime manufactured by JEOL.
[0321] Determination conditions:
[0322] Vacc: 5kV, Coating: W, UED image
[0323] In the Rydberg analysis, the precipitated crystals are Li6.5 (Si,P)O 8 In this case, the crystallinity is 18.2% and the crystal grain size is 15 nm.
[0324] Although the present invention is described in detail with reference to specific embodiments, various changes and modifications can be made without departing from the spirit and scope of the present invention, which is obvious to those skilled in the art. It should be noted that this application is based on Japanese patent applications (Japanese patent applications 2020-140347) filed on August 21, 2020 and Japanese patent applications (Japanese patent applications 2021-090475) filed on May 28, 2021, and the full texts of these applications are incorporated herein by reference. In addition, all references cited herein are incorporated herein as a whole.
Claims
1. A chemically strengthened glass, wherein: The haze value of the chemically strengthened glass converted to a thickness of 0.7 mm is 0.5% or less. The surface compressive stress value of the chemically strengthened glass is greater than 400 MPa. The compressive stress layer depth of the chemically strengthened glass is greater than 70 μm, and The ST limit of the chemically strengthened glass determined by the following test method is 18000 MPa・μm to 30000 MPa・μm. The chemically strengthened glass is glass-ceramics, The basic composition of chemically strengthened glass, expressed in mole % on an oxide basis, is: 52%~59.5% SiO2, 22% to 35% Li2O, 3% to 8% Al2O3, 1% to 4.2% P2O5, 0%~4% Y2O3, 0% to 4% B2O3, 1% to 2.5% Na2O, 2.5% to 4.5% ZrO2, and 0%~2% SnO2, The total amount of SiO2, Al2O3, P2O5 and B2O3 is 60% to 70%. The total content of Na2O and K2O is more than 2%, The ratio of the total amount of Li2O, Na2O and K2O to the total amount of SiO2, Al2O3, P2O5 and B2O3 is 0.30-0.
60. The ratio of K2O content to the total content of Li2O, Na2O and K2O (R2O) is 0.10 or less. The content ratio of R2O to ZrO2 is 0.04 to 0.
3. Test methods As the test glass plates, a plurality of test glass plates having different tensile stress integral values, i.e., ST values, were prepared by subjecting a 15 mm square glass plate, 0.7 mm thick, and mirror-finished on the surface to chemical strengthening treatment under various conditions. Using a Vickers testing machine, a diamond indenter with a front angle of 90° was driven into the center of the test glass plate to break the glass plate, and the number of fragments was taken as the number of broken pieces. The test was started with a diamond indenter load of 1 kgf. If the glass plate did not break, the load was increased by 1 kgf at a time, and the test was repeated until the glass plate broke. The number of broken pieces at the initial break was counted. The number of broken pieces was plotted against the ST value of the test glass plate, and the ST value when the number of broken pieces reached 10 was read and used as the ST limit.
2. The chemically strengthened glass according to claim 1, wherein: Al2O3 is more than 5%.
3. The chemically strengthened glass according to claim 1 or 2, wherein: The average thermal expansion coefficient of the chemically strengthened glass at 50°C to 350°C is 80×10 -7 / ℃~100×10 -7 / ℃.
4. A semiconductor support substrate, wherein: The semiconductor supporting substrate includes the chemically strengthened glass according to any one of claims 1 to 3.
5. A glass-ceramic, wherein: The basic composition of the glass-ceramics comprises, in terms of mole % based on oxides: 52%~59.5% SiO2, 22% to 35% Li2O, 3% to 8% Al2O3, 1% to 4.2% P2O5, 0%~4% Y2O3, 0% to 4% B2O3, 1% to 2.5% Na2O, 2.5% to 4.5% ZrO2, and 0%~2% SnO2, The total amount of SiO2, Al2O3, P2O5 and B2O3 is 60% to 70%. The total content of Na2O and K2O is more than 2%, The ratio of the total amount of Li2O, Na2O and K2O to the total amount of SiO2, Al2O3, P2O5 and B2O3 is 0.30-0.
60. The ratio of K2O content to the total content of Li2O, Na2O and K2O (R2O) is 0.10 or less. The content ratio of R2O to ZrO2 is 0.04 to 0.
3. The haze value of the microcrystalline glass converted to a thickness of 0.7 mm is less than 0.5%, and The ST limit of the glass-ceramics determined by the following test method is 18000 MPa・μm or more. Test methods As the test glass plates, a plurality of test glass plates having different tensile stress integral values, i.e., ST values, were prepared by subjecting a 15 mm square glass plate, 0.7 mm thick, and mirror-finished on the surface to chemical strengthening treatment under various conditions. Using a Vickers testing machine, a diamond indenter with a front angle of 90° was driven into the center of the test glass plate to break the glass plate, and the number of fragments was taken as the number of broken pieces. The test was started with a diamond indenter load of 1 kgf. If the glass plate did not break, the load was increased by 1 kgf at a time, and the test was repeated until the glass plate broke. The number of broken pieces at the initial break was counted. The number of broken pieces was plotted against the ST value of the test glass plate, and the ST value when the number of broken pieces reached 10 was read and used as the ST limit.
6. The glass-ceramic according to claim 5, wherein: Al2O3 is more than 5%.
7. A method for manufacturing glass-ceramics, wherein: Heat treatment is performed to keep the glass at a temperature of 450°C or higher and 800°C or lower. The glass contains, in mole % based on oxides: 52%~59.5% SiO2, 22% to 35% Li2O, 3% to 8% Al2O3, 1% to 4.2% P2O5, 0%~4% Y2O3, 0% to 4% B2O3, 1% to 2.5% Na2O, 2.5% to 4.5% ZrO2, and 0%~2% SnO2, The total amount of SiO2, Al2O3, P2O5 and B2O3 is 60% to 70%. The total content of Na2O and K2O is more than 2%, The ratio of the total amount of Li2O, Na2O and K2O to the total amount of SiO2, Al2O3, P2O5 and B2O3 is 0.30-0.
60. The ratio of K2O content to the total content of Li2O, Na2O and K2O (R2O) is 0.10 or less. The content ratio of R2O to ZrO2, ZrO2 / R2O, is 0.04 to 0.
3.
8. A method for producing a chemically strengthened glass article, wherein: An article comprising the glass-ceramics according to claim 5 is chemically strengthened.
9. A semiconductor support substrate, wherein: The semiconductor support substrate includes the glass-ceramics according to claim 5 .
Citation Information
Patent Citations
Crop management system and crop management method
JP2020140347A
Electric apparatus and dishwasher
JP2021090475A
Chemically strengthened glass and production method therefor
WO2019022035A1
Crystallized glass, chemically strengthened glass, and semiconductor substrate
WO2020161949A1